Educação Física no PPGMH/UFRGS: uma visão a partir da análise de citações e perfil dos pesquisadores - Ivone Job (2006)
In the present study, we analyzed the professors profile and 1,171 citations of dissertations of the Graduate Program in Human Movement Science (GPHMS) of the Escola de Educação Física, Universidade Federal do Rio Grande do Sul, completed between the years 2003 and 2004. The purpose was to identify characteristics of the sources used by the authors; to contribute to the epistemological studies of the field, from the point of view of information science; and to characterize textual elements, exploiting their potentialities, aiming at the knowledge of the scientific field of physical education. The study focused on the discovery of the intertextuality and interdisciplinarity of the area. The theoretical foundation was build from diverse fields of study: from history, more specifically from the clue-following method, used in this study; from sociology of knowledge, with emphasis on sociology of science; from information sciences, specially bibliometry, citation analysis, and scientific communication, approaching three important theories about scientific communities (Kuhn, Bordieu, and Knorr-Cetina); and, finally, from physical education. From the first field, we obtained the foundation for the use of clue-following data and factors to unveil a reality; with the second, we became aware of the course followed by knowledge for its settlement in the scientific and academic world, as well as the origin of the citations in documents. Of the third, we used the tools and techniques, as well as the theoretical constructions regarding scientific communication and academic output. The fourth corresponds to the object of the present research the field of study referred as human movement by some authors and as physical education by others , which was developed in its general and local historical aspects. The following indicators were identified and related: type of authorship, cited authors, type of document, idiom, obsolescence, journal title, and topic of the citations. The 1,171 references studied revealed that: the article it the most used type of document (49.53%); English is the predominant idiom in the documents of the citations (55.85%); the publications in the period 1991-2000 cover 56.02% of the citations, with their peak in 1998 and probable health-life of the documents in the field around five years; 41.76% of the cited documents were written by one single author; and 54.23% were written by more than one author. The predominant topics that make the interdisciplinarity of the field are the following, in this order: social sciences, medicine, biophysics, sports, education, philosophy, teaching, and physical fitness. A total of 1,825 different authors was cited. Morin, Foucault, and Lapierre are among the most representative and evidence a great dispersion in the field. There is dispersion in both authors and periodical titles: 80.71% were cited only once; and 37.11% were cited more than once. Only six periodicals five international and one national were cited in more than one dissertation. The predominant research lines in the GPHMS are from the concentration area Human movement, health, and performance, which privileges the biological character. The same occurs with the number of dissertations, with 89% of them in the same concentration area. There is a need for a greater national output in theoretical terms for the field of physical education. The analysis allowed verifying that the scientific fields and their respective communities develop theirselves in a contingent and contextual way. The clue-following method enabled to link the clues presented by the variables analyzed and showed to be a possible method in studies on bibliometry and citation analysis. There are clues of habits of domestic citation and endogeny, but it was not proved in the present study.